2004
DOI: 10.1007/bf03392995
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Untaught Mands or Tacts of Novel Adjective-Object Pairs as a Function of Instructional History

Abstract: We tested the effects of multiple exemplar instruction (MEI) on the emergence of untaught mands or tacts of adjective-object pairs in a multiple-probe design across four students with autism/developmental disabilities. None of the students emitted either mands or tacts for three sets of three adjective-object pairs (word sets counterbalanced across students and conditions) in pre-experimental probe trials. In the baseline phase, either mands or tacts were taught for the first adjective-object pairs to each stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
91
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 19 publications
10
91
0
12
Order By: Relevance
“…The terms refer generally to similar operations. Some possible differences are that in both the MEI research described by Becker (1992) and in the research on the emergence of Naming (Fiorile & Greer, 2007;, 2007, the emergence of tacts from learning mands and vice versa (Nuzzolo-Gomez & Greer, 2004), and the emergence of writing from saying and vice versa (Greer, Yuan et al, 2005) consistently used the correction component of the learn unit (Ingham & Greer, 1992); whereas, in the multiple exemplar training this may have not been the case. Moreover, the MEI used in the studies on Naming and the joining of saying and writing involve MEI across response types along with MEI for the visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The terms refer generally to similar operations. Some possible differences are that in both the MEI research described by Becker (1992) and in the research on the emergence of Naming (Fiorile & Greer, 2007;, 2007, the emergence of tacts from learning mands and vice versa (Nuzzolo-Gomez & Greer, 2004), and the emergence of writing from saying and vice versa (Greer, Yuan et al, 2005) consistently used the correction component of the learn unit (Ingham & Greer, 1992); whereas, in the multiple exemplar training this may have not been the case. Moreover, the MEI used in the studies on Naming and the joining of saying and writing involve MEI across response types along with MEI for the visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In another but somewhat different application of MEI, Nuzzolo-Gomez and Greer (2004) found that MEI across establishing operations with a subset of responses led to the untaught usage of vocal mands or tacts with children for whom the tact and mand functions were independent prior to the MEI intervention. In this case, single responses came to be controlled for novel production as a function of the establishing operations tied to different verbal functions.…”
Section: R Douglas Greer Columbia University Teachers College and Gmentioning
confidence: 99%
“…However, these studies subsequently demonstrated emergent responding through the use of transfer-of-stimulus-control procedures (Partington et al, 1994), exemplar training (Hall & Sundberg, 1987;Sigafoos et al, 1990), or multiple exemplar training (Nuzzolo-gomez & greer, 2004). In general, these studies showed that emergent responding was demonstrated following specific training procedures to transfer control from the trained to the untrained operant.…”
mentioning
confidence: 98%
“…The goal of much of this research has been to establish effective communicationtraining programs for persons with developmental disabilities (Sundberg & Partington, 1998). Researchers in this area have often focused on establishing "emergent" verbal behavior in which a response acquired under the controlling conditions of one verbal operant transfers to the conditions of another without direct instruction (Hernandez, Hanley, Ingvarsson, & Tiger, 2007;Nuzzolo-gomez & greer, 2004;Rosales & Rehfeldt, 2007). It has been observed that children with autism spectrum disorders (ASD) lack this type of emergent responding.…”
mentioning
confidence: 99%
See 1 more Smart Citation